2023
DOI: 10.1002/gj.4683
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Susceptibility mapping using random forest and extreme gradient boosting: A case study of Fengjie, Chongqing

Abstract: Landslide susceptibility analysis can provide theoretical support for landslide risk management. However, some susceptibility analyses are not sufficiently interpretable. Moreover, the accuracy of many research methods needs to be improved. Therefore, this study can supplement these deficiencies. This study aims to research the evaluation effects of random forest (RF) and extreme gradient boosting (XGBoost) classifier models on landslide susceptibility, and to compare their applicability in Fengjie County, Cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Assessing landslide susceptibility is crucial for managing landslide risks, but some analyses lack interpretability and have low accuracy (Can et al, 2021; Demir, 2019; Kavzoglu & Teke, 2022; Sun et al, 2021). Zhang, He, et al (2023) aim to address these deficiencies by evaluating the effectiveness of random forest (RF) and extreme gradient boosting (XGBoost) models in predicting landslide susceptibility in Fengjie County, a typical landslide‐prone area in southwest China. Field investigations yielded 1624 landslide occurrences from 1980 to 2020, and a geospatial database of 16 conditional factors was constructed.…”
Section: Research Outputs Of This Special Issuementioning
confidence: 99%
“…Assessing landslide susceptibility is crucial for managing landslide risks, but some analyses lack interpretability and have low accuracy (Can et al, 2021; Demir, 2019; Kavzoglu & Teke, 2022; Sun et al, 2021). Zhang, He, et al (2023) aim to address these deficiencies by evaluating the effectiveness of random forest (RF) and extreme gradient boosting (XGBoost) models in predicting landslide susceptibility in Fengjie County, a typical landslide‐prone area in southwest China. Field investigations yielded 1624 landslide occurrences from 1980 to 2020, and a geospatial database of 16 conditional factors was constructed.…”
Section: Research Outputs Of This Special Issuementioning
confidence: 99%
“…Du et al and Jia et al further conducted experimental research on dumping perilous rock and found that the natural vibration frequency is closely related to the stability [30][31][32][33]. However, the above research has just started and is in the experimental stage, and the theory has not yet been perfected [34,35]. And the above test found that the dynamic characteristic parameters of the perilous rock are closely related to the stability [36].…”
Section: Introductionmentioning
confidence: 99%
“…Landslide deformation is mainly caused by a variety of factors. The complex process of landslide deformation makes it difficult to accurately distinguish the stages of landslide deformation [18][19][20][21]. Therefore, the traditional empirical means are no longer applicable.…”
Section: Introductionmentioning
confidence: 99%